God and Purported Logical Arguments from Evil and Suffering - Sterba, James P. (New blackfriars, 2024)
Logical arguments from evil against the existence of God are the strongest form of arguments from evil. They maintain that the all-good, all-powerful God of traditional theism is logically incompatible with the evil in the world. Given that the most well-known logical argument from evil remains the argument put forward by John Mackie over fifty years ago, I begin by setting out Mackie’s argument in detail as well as Alvin Plantinga’s well-regarded critique of it. I then discuss Mackie’s not well-known confusing response to Plantinga’s critique along with attempts by Hugh LaFollette and Quentin Smith to support Mackie’s argument, which fail to take into account Mackie’s own concession to Plantinga’s critique. I then discuss my own attempt in 2019 to provide a Mackie-style logical argument from evil and the reception it has received. I end by suggesting that further discussion might best be pursued by taking up the related question of whether an objective ethics can by adequately supported without appealing to the existence of the God of traditional theism.